STUDI KEMAMPUAN SISWA KELAS DUA SMKN 2 PEKANBARU DALAM MENULIS TEKS PROSEDUR - Susanti, Fitri; Delfi, Syofia; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The aim of this study is to find out the ability of the second year students of SMKN 2 Pekanbaru in writing procedure texts. The population of this research is all of the second year students which consisted of 332 students. There were 34 students who participated in this study as sample. The instrument was a test adapted from authentic material. The frame of the test was covered by 5 components such as, grammar, organization, mechanics, vocabulary, and content. The students write a procedure text based on the topic given. To analyze the data, the raw score of the students was calculated and the level of ability was identified by using the classification of ability level by Arikunto (2003). The result showed that the ability of the second year students of SMKN 2 Pekanbaru in writing procedure texts was at Mediocre level with mean score 74,33. Therefore, it can be concluded that most of the students were able to writing procedure texts. To reach this, the students were suggested to do more practice in writing activity, particulary in writing procedure text.Key Words: Writing Ability, Writing Ability, Procedure Text